Molecular genetic basis of the human Forssman glycolipid antigen negativity - Yamamoto, Miyako (Nature Publishing Group, 2012)
Forssman heterophilic glycolipid antigen has structural similarity to the histo-blood group A antigen, and the GBGT1 gene encoding the Forssman glycolipid synthetase (FS) is evolutionarily related to the ABO gene. The antigen is present in various species, but not in others including humans. We have elucidated the molecular genetic basis of the Forssman antigen negativity in humans. In the human GBGT1 gene, we identified two common inactivating missense mutations (c.688G>A [p.Gly230Ser] and c.887A>G [p.Gln296Arg]). The reversion of the two mutations fully restored the glycosyltransferase activity to synthesize the Forssman antigen in vitro. These glycine and glutamine residues are conserved among functional GBGT1 genes in Forssman-positive species. Furthermore, the glycine and serine residues represent those at the corresponding position of the human blood group A and B transferases with GalNAc and galactose specificity, respectively, implicating the crucial role the glycine residue may play in the FS α1,3-GalNAc transferase activity.